Faktor yang Memengaruhi Non Performing Financing pada Bank Umum Syariah BUMD di Indonesia - Tsania, Nurfadhila; Tamara, Destian Arshad Darulmalshah; ., Setiawan (Journal of Islamic Economics and Business, 2021)
The purpose of this study was to determine the influence ofÂ Capital Adequacy Ratio (CAR), Financing to Deposit RatioÂ (FDR), Operational Expenses on Operational FinancingÂ (BOPO) and Gross Regional Domestic Product (GRDP)Â partially on Non-Performing Financing (NPF) in Sharia Bank ofÂ Municipally-Owned Corporations in Indonesia The dataÂ analysis technique used is path analysis. This study selected aÂ sample with a purposive sampling method and selected threeÂ Islamic Commercial Banks to be used. The data used isÂ secondary data sourced from the financial reports of IslamicÂ Commercial Banks and the Central Statistics Agency whichÂ have been published and collected using documentationÂ techniques or direct quotations. The results of this studyÂ indicate that CAR, FDR, and GRDP have no effect on NPFÂ meanwhile BOPO has an effect on NPF.